Os subalternos na esfera pública: racionalidade, igualdade e justiça na primeira onda do movimento homossexual brasileiro - Alves, Juliana Barros [UNIFESP] (2020)
This work aims to shed light on the activist trajectory of the First Wave of the Brazilian Homosexual Movement (1978-1983) in the metropolitan region of São Paulo, based on the theoretical framework coined by Habermas (2014), Fraser (1989; 1997; 2009) and Michael Warner (2005). The scrutiny of such a trajectory is necessary to deepen the reflection about the entry of the claim for rights to sexual and gender diversity. Testimonies from ex-members of groups of homosexuals organized from the period will be analyzed, collected in a qualitative interview and documents from AEL IFCH UNICAMP.